Provide security for wireless mobile networks with different multiple access Techniques and MANET Network - Uma Shankari, E; Rajashekhar Reddy, S; Aditya Sharma, P; Geetha, G (International Journal of Engineering and Technology, 2018)
The most recent versatile innovation of new features in mobile technology is needed for advancement of the Internet, for the features of better, quicker access of information. Cell division subscribers pay additional costs for instant messaging, stock quotes, and Furthermore easy internet access on their phones. In order to support such a capable system, we need pervasive, high-speed remote connectivity. Bluetooth and 802.11 are currently existing techniques for providing high speed digital wireless connectivity. The extension of 4G technology gave scope for mobile communications. Mobile is not only a portable talking gadget but also utilized for multiple distinctive purposes.4G offers higher data rates for consistent roaming. That portable mobile client might communicate without any disturbance due to network problems. In this process report we discuss different tests that 4G will facing and also gives the solutions for those problems. We recommend our own method for enhancing QoS On 4G eventually by utilizing both SMIP and SIP. We recommend that by utilizing such plan we might accomplish better QoS throughout that process of handover.Â